Progressivism, Collegialism and Autonomy in Muhammadiyah: Threats and Solution - Fantika Febry Puspitasari; Supriyanto Supriyanto; Ahmad Sulaiman (Universitas Muhammadiyah Magelang, 2020)
Muhammadiyah is one of the world's largest Islamic movement organizations, contributing to a variety of important areas of life for Indonesians. Muhammadiyah promotes three main characteristics based on community development: progressiveism, collegialism, and autonomy. Unfortunately, as Islamic populism grew stronger, Muhammadiyah became engulfed in a political vortex, endangering the stability of its cadres and giving the public the impression that the government could control the organization. This article evaluates the threats that cause these values to deteriorate and offers treatment options. The solutions offered to maintain the principles of progressiveism, collegialism, and autonomy are to rejuvenate the leadership, build distance from politics, develop community funds, and build supporting business units, according to literature studies and observations in several areas. Furthermore, political education as an effort to formulate political theology for Muhammadiyah members is required so that the big ship of Muhammadiyah does not become divided due to differences in political views and can increasingly contribute to politics at the local-national level without jeopardizing its integrity as a movement organization.